2009
DOI: 10.1016/j.crvi.2009.03.009
|View full text |Cite
|
Sign up to set email alerts
|

ABA, GA3, and nitrate may control seed germination of Crithmum maritimum (Apiaceae) under saline conditions

Abstract: Impaired germination is common among halophyte seeds exposed to salt stress, partly resulting from the salt-induced reduction of the growth regulator contents in seeds. Thus, the understanding of hormonal regulation during the germination process is a main key: (i) to overcome the mechanisms by which NaCl-salinity inhibit germination; and (ii) to improve the germination of these species when challenged with NaCl. In the present investigation, the effects of ABA, GA 3 , NO − 3 , and NH + 4 on the germination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 21 publications
1
56
0
4
Order By: Relevance
“…Bajehbaj (2010) showed that KNO 3 primed seeds increased seed germination percentage and seedlings growth in sunflower cultivars under salinity conditions by promoting K and Ca accumulation and inducing osmoregulation by the accumulation of proline. A positive effect of KNO 3 on germination in saline condition was also documented in halophytes like Suaeda salsa (Li et al, 2005) and Crithmum maritimum (Atia et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…Bajehbaj (2010) showed that KNO 3 primed seeds increased seed germination percentage and seedlings growth in sunflower cultivars under salinity conditions by promoting K and Ca accumulation and inducing osmoregulation by the accumulation of proline. A positive effect of KNO 3 on germination in saline condition was also documented in halophytes like Suaeda salsa (Li et al, 2005) and Crithmum maritimum (Atia et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, salinity can affect germination by reducing the N content available for embryo growth in seeds, as it delays the mobilization of protein stores, delaying the development of the new plant (Voigt et al, 2009). Atia et al (2009) reported that NO 3 -derived from the salts NaNO 3 and KNO 3 increased germination and the germination speed index of both control and stressed seeds (100 mM NaCl). Abdelgabir et al (2012) demonstrated that NO 3 -priming promoted the longitudinal growth of the roots of Jatropha curcas L. seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Even though benefits can be optimal using the appropriate Ψs for seed priming, the benefits can still be improved by the action of NO 3 -derived from the salt NaNO 3 . Atia et al (2009), usied KNO 3 and reported increases of 35% and 330% in the percentage of germination in Crithmum maritimum seeded in media containing 100 mM and 200 mM NaCl, respectively. Positive effects on germination with the use of nitrogenous salts have also been documented in halophytes such as Atriplex griffithii (Khan et al, 2000), Zygophyllum simplex L. (Khan et al, 2002) and Suaeda salsa (Li et al, 2005) as well as in tolerant species such as Lactuca sativa (Hendricks et al, 1974) and Avena fatua (McIntyre et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations